An unprecedented large-scale survey of honey bee mitochondrial diversity in Europe: c-lineage dominance and the need for conservation efforts - Li, Fernanda (2024)
Europe is home to ten Apis mellifera subspecies, which belong to three mitochondrial lineages: the Western European (M), Eastern European (C), and African (A). However, the long-standing human-mediated movement of queens, primarily of C-lineage ancestry, has threatened the genetic integrity of many of these native subspecies through introgression and replacement. This has led to the establishment of conservation programs to recover the native lines in some European countries. The maternally-inherited mitochondrial DNA (mtDNA), particularly the highly polymorphic intergenic region tRNAleu-cox2, has been the marker of choice for assessing honey bee variation and introgression at large geographical scales. Herein, we will show the results of the tRNAleu-cox2 variation obtained from over 1200 colonies sampled across the range of the ten subspecies and covering 33 European countries. These revealed that apart from a few countries (Portugal, Spain, and Ireland) and isolated protected populations, European populations are predominantly dominated by C-lineage haplotypes, and many native subspecies exhibit a signature of C-derived introgression. In conclusion, this unprecedented survey of honey bee diversity across Europe underscores the concerning dominance of C-lineage genetic variation, highlighting the urgent need for strategic conservation efforts to preserve the native genetic diversity of Apis mellifera.